Incarceration and older women: giving back not giving up - White, Regina Lynn (Bristol University Press, 2023)
Generativity or 'giving back' is regarded as a common life stage, occurring for many around middle age. For the first time, this book offers qualitative research on the lives and social relationships of older imprisoned women. In-depth interviews with 29 female prisoners in the south-eastern United States show that older women both engage in generative behaviours in prison and also wish to do so upon their release. As prisoners continue to age, the US finds itself at a crossroads on prison reform, with potential decarceration beginning with older prisoners. The COVID-19 pandemic has led many to consider how to thrive under difficult circumstances and in stressing the resilience of older incarcerated women, this book envisions what this could look like